Nonlinear resonators for all-optical signal processing - Maitra, Ayan (Karlsruhe Series in Photonics & Communications, 2007)
All-optical signal processing will be used in future communication networks. We discuss a new and generic scheme for such devices. The basic configuration comprises an asymmetric resonator within an active or passive nonlinear medium. This arrangement enables all-optical flip-flop operation and switching with a reduced threshold. In addition, a novel optical isolator concept based on resonator asymmetries is is introduced. The model is also applicable to photonic crystal based resonators.